Chainey, Carys - (:unkn) unknown (My University, 2025)
Dr Carys Chainey is a postdoctoral research fellow and coordinator of the Parenting and Family Research Alliance. Her research investigates the links between adverse childhood experiences, parenting, and wellbeing, across the life course and across generations. Carys has expertise in the design, implementation, and analysis of quantitative, qualitative, and mixed methods research. She is an accredited facilitator of the Triple P Positive Parenting Program and has contributed to a wide range of empirical studies and evaluations for the government. Carys’ current projects include analyses of large survey datasets (e.g. the Longitudinal Study of Australian Children, National Health Survey) and novel survey datasets to explore how intergenerational adversity and parenting influence the wellbeing of adolescents and emerging adults. She is also contributing to the Every Family Triple P population trial, and preliminary trials of a new intervention targeting caregivers with a history of adversity, Family Life Skills Triple P.

Dr Carys Chainey is a postdoctoral research fellow and coordinator of the Parenting and Family Research Alliance. Her research investigates the links between adverse childhood experiences, parenting, and wellbeing, across the life course and across generations. Carys has expertise in the design, implementation, and analysis of quantitative, qualitative, and mixed methods research. She is an accredited facilitator of the Triple P Positive Parenting Program and has contributed to a wide range of empirical studies and evaluations for the government. Carys’ current projects include analyses of large survey datasets (e.g. the Longitudinal Study of Australian Children, National Health Survey) and novel survey datasets to explore how intergenerational adversity and parenting influence the wellbeing of adolescents and emerging adults. She is also contributing to the Every Family Triple P population trial, and preliminary trials of a new intervention targeting caregivers with a history of adversity, Family Life Skills Triple P.